Soka Education Philosophy as a Foundation for Teacher Preparation in Creating Inclusive Education - Agbenyega, Joseph Seyram; Ikegami, Kiiko; Rivalland, Corine (International Perspectives on Inclusive Education, 2021)
Current global shifts in education towards inclusive early childhood education are deeply engineered by the crisis of educational exclusion. In responding to exclusion, teachers have mainly utilized dominant western theories to plan and implement inclusive teaching. In this chapter, we draw on a non-western philosophy, a Nichiren Buddhist (Soka) philosophy, to provide a ‘kaleidoscopic’ lens through which to create inclusive educational learning spaces that engender full participation of all children. The Soka education philosophy is a humanist concept which can guide teachers when preparing to create inclusive education. The aims of this chapter are threefold: The first is an exploration of the Nichiren Buddhist (Soka) philosophy. The second aim is to highlight how this philosophy can enable teachers to unleash the unlimited potential of children in inclusive learning settings. Thirdly, we argue that grounding early childhood teacher education in this philosophy can help improve the effectiveness of inclusive educational experience for all children.

Challenges and Learning Strategy for young children with special needs during the pandemic in Indonesia - Fridani, L.; Ikegami, Kiiko (Anthology Challenges in Management of Early Childhood Education during Pandemic, 2021)

Students’ wellbeing during the Covid-19 pandemic - Ikegami, Kiiko (The International Webinar of University Riau Conference, 2021)